Phthriasis Palpebrarum Mimicking Lid Eczema and Blepharitis - Turgut, Burak; Kurt, Julide; Catak, Onur; Demir, Tamer (Hindawi Ltd, 2009)
Phthiriasis palpebrarum (PP) is a rare eyelid infestation caused by phthirus pubis. We report a case of PP mimicking lid eczema and blepharitis. A 68-year-old woman had moderate itching in both eyes. Her initial diagnosis was considered to be lid eczema or blepharitis because of findings similar to exfoliative lesions and color changes in eyelids and to excretions over eyelashes. Careful observation revealed many lice and translucent nits, protuberances and hyperpigmentary changes, and the buried lice in both eyelids. No hyperemia or secretion was observed on the lids and in the conjunctiva in both eyes. The patient was treated with pilocarpine hydrochloride 4% drops. At the end of the first week, no louse or nit was present. Although it was known that PP is a rare cause of blepharoconjunctivitis, it might observe as an isolated infestation of the eyelids and this condition can easily be misdiagnosed as lid eczema and blepharitis. Copyright (C) 2009 Burak Turgut et al.